MODELING QUEUING SYSTEM OF INTERACTION BETWEEN TERMINAL DEVICES AND SERVICES PROVIDERS IN THE BANK - Ivan A. Mnatsakanyan (Статистика и экономика, 2016)
The article focuses on the development of mathematical models and tools to optimize the system of queuing at the bank. The article discusses the mathematical aspects that will achieve redistribution of transaction flow, reduce the time of the request in the queue, increase the bank’s profit and gain competitive advantage.